Gambaran Sikap Percaya Diri Korban Bullying Verbal Di MAN 3 Sleman - Tutik Ernawati; Nararya Rahadyan Budiyono (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
Verbal bullying, namely bullying that is carried out by mocking or throwing words that lead to excessive humiliation which causes excessive fear and a decrease in self-confidence in the victim. The purpose of this study was to determine the description of the self-confidence of MAN 3 Sleman verbal bullying victims. The method used in this research is descriptive qualitative. The subjects in this study amounted to 7 students who were victims of verbal bullying and 21 students as observers as observers of the validity of verbal bullying events and see the self-confidence of victims of bullying. The results of this study indicate that verbal bullying behavior has an impact on the self-confidence of victims of bullying, namely there are victims of bullying who experience a decrease in self-confidence, such as when doing activities or learning at school, victims become afraid to express their opinions or arguments, prefer to be alone, quiet, and even dare not go to school, but there are also victims of verbal bullying who experience increased self-confidence because the bullying behavior becomes motivation. The benefits of this research are to provide an overview and also knowledge about the description of the self-confidence of victims of verbal bullying MAN 3 Sleman so as to add theoretical references regarding the impact, anticipation and efforts regarding verbal bullying.